Reply to Berlanga et al. (DOI 10.1515/cclm-2014-0420) - Joannes F.M. Jacobs; Rein M.J. Hoedemakers; Henk te Velthuis (Clinical Chemistry and Laboratory Medicine (CCLM), 2014)
Objectives Thalassemia and hemoglobinopathies are significant genetic disorders in Thailand. Routine diagnostic methods including complete blood count (CBC), hemoglobin (Hb) analysis, and targeted PCR, are effective for detecting common mutations but limited sensitivity for rare and unstable variants, and complex genotypes. Long-read nanopore sequencing may overcome these limitations in a single analytical workflow. This study evaluated the feasibility of CycloneSEQ nanopore sequencing and compared its diagnostic performance with routine methods and DNA nanoball (DNB) short-read sequencing. Methods 150 EDTA blood samples submitted for routine thalassemia diagnosis were randomly selected. Routine diagnosis included CBC, Hb analysis, and targeted PCR for common α- and β-thalassemia mutations. All samples were further analyzed using DNB and CycloneSEQ sequencing. Diagnostic performance, turnaround time, and cost were compared. Results Among the three methods, 78.7 % of cases showed concordant results, while 20.0 % could not be fully characterized using routine diagnostic panels. Sequencing methods identified the additional mutations including α + -thalassemia (-α 3.7 ) and rare variants such as Hb Dhonburi, Hb Westmead, etc. Discordant results were observed in 1.3 % of cases. CycloneSEQ required approximately 3-5 days for analysis, whereas DNB sequencing required 10-12 days and routine methods required up to 14 days. Although sequencing costs were approximately 1.7-fold higher than conventional testing, comprehensive mutation detection was achieved in a single step. Conclusions CycloneSEQ nanopore sequencing demonstrated enhanced diagnostic performance compared with conventional methods by enabling a single analytical workflow, and shorter turnaround time. This is particularly beneficial for thalassemia management in Thailand and other high-prevalence areas.